2016
DOI: 10.1111/jvh.12573
|View full text |Cite
|
Sign up to set email alerts
|

Associations of human leucocyte antigen class IIDQB1 alleles with hepatitis C virus infection in Egyptian population: a multicentre family‐based study

Abstract: Hepatitis C infection is a global pandemic. HLA-DQB1 alleles are believed to have an effective role in immune response against HCV including susceptibility to or protection from this infection. The aim of this study was to investigate the contribution of HLA-DQB1 alleles in the outcome of HCV genotype-4 infection through a family-based association study. Egyptian families with HCV (324) were recruited for this study (324 index positive for RNA-HCV, 225 positive relatives representing chronic hepatitis C cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Concerning HLA‐DQB1*03:01 allele, identified as a risk factor for OLI, previous studies showed conflicting results: Whereas in chronic hepatitis, this allele has been correlated in some instances with HCV clearance (Huang et al ., ; Thio et al ., ; El‐Bendary et al ., ), other authors have reported a link between HLA‐DQB1*03:01 and HPV6 infection (Chen et al ., ). Notably, this HPV subtype, despite being considered as low risk for cervical cancer, is established to cause genital lesions and to be found in the semen (Lyu et al ., ; Flores‐Díaz et al ., ).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Concerning HLA‐DQB1*03:01 allele, identified as a risk factor for OLI, previous studies showed conflicting results: Whereas in chronic hepatitis, this allele has been correlated in some instances with HCV clearance (Huang et al ., ; Thio et al ., ; El‐Bendary et al ., ), other authors have reported a link between HLA‐DQB1*03:01 and HPV6 infection (Chen et al ., ). Notably, this HPV subtype, despite being considered as low risk for cervical cancer, is established to cause genital lesions and to be found in the semen (Lyu et al ., ; Flores‐Díaz et al ., ).…”
Section: Discussionmentioning
confidence: 84%
“…Importantly, several alleles of HLA class I and II genes have already been correlated with sexually transmitted diseases (STD) caused by Neisseria gonorrhoeae (gonorrhea) (Ness et al ., ; Geisler et al ., ), Chlamydia trachomatis (Ness et al., ; Olson et al., ), Treponema pallidum (syphilis) (Zhuang et al ., ; Jiang et al ., ), human immunodeficiency virus (HIV) (Raghavan et al ., ; Rallón et al ., ), human papillomavirus (HPV) (Chen et al ., ), hepatitis B virus (HBV) (Nishida et al ., ), and hepatitis C virus (HCV) (Huang et al ., ; Thio et al ., ; El‐Bendary et al ., ). Such microbial agents per se and together with activated immunological processes can lead to anatomical obstruction, compromise normal gland function, affect the availability of diverse seminal components, and interfere in sperm viability (du Plessis et al ., ; Flint et al ., ; Weidner et al ., ; Gimenes et al ., 2014a; Bezold et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Previous research has shown that low viral diversity and strong CD4+ T-cell response targeting a broad range of virus antigenic epitopes are connection with spontaneous viral clearance (SVC), while infectious agents can lead to incompetent T-cell response and persistent infection through a variety of complex mechanisms [ 28 ]. Furthermore, the epitopes of CD4+ T-cell are highly promiscuous and can often be restricted by a variety of different HLA class II molecules [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…MHC class I and II antigens are the central to the host immune response, which make them ideal candidate genes to investigate their association with HCV infection (18). HLA is a crucial genetic factor that initiates and regulates immune response through presenting endogenous and exogenous antigen to T lymphocytes (12). An increased and broadly multi-specific T-cell response is critical to get a favorable outcome.…”
Section: Discussionmentioning
confidence: 99%
“…A genetic association study clarified that the human leukocyte antigen (HLA) was an essential genetic factor that regulated immune response and may be one of the tactics used by HCV to avoid immune clearance (12). Furthermore, various HLA alleles involved in the immune response were demonstrated to be linked to spontaneous clearance of HCV infection and even be potentially predictive for HCV treatment response (13).…”
Section: Introductionmentioning
confidence: 99%